Vanadium sodium fluorophosphate nanofiber positive electrode composite material as well as preparation method and application thereof
By using polyphenol compounds and electrospinning technology in sodium ion batteries to coat sodium vanadium fluorine phosphate nanoparticles to form nanofiber positive electrode composite materials, the problems of poor conductivity of sodium vanadium fluorine phosphate and uneven carbon coating are solved, significantly Improves battery performance and life.
Patent Information
- Application Number
- CN202411317977.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-02-07
AI Technical Summary
Sodium vanadium fluorophosphate has poor electrical conductivity in sodium ion batteries and is unevenly coated with carbon, which leads to easy agglomeration of materials and affects electrochemical reaction efficiency and battery performance.
By using polyphenol compounds as reducing agents and combined with electrospinning technology, a positive electrode composite material of vanadium fluorine phosphate nanofibers is formed, and the vanadium fluorine phosphate nanoparticles are uniformly coated inside the nanofibers to form a continuous fiber network structure.
It improves the conductivity and structural stability of the material, enhances the energy density and rate performance of the battery, extends the cycle life of the battery, and reduces the volume expansion of the material.
Smart Images

Figure CN119400814A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of battery materials and electrochemical energy storage, and relates to a sodium vanadium fluorophosphate nanofiber positive electrode composite material and a preparation method and application thereof, in particular to the application of a sodium vanadium fluorophosphate nanofiber positive electrode composite material in a sodium ion battery. Background Art
[0002] With the growing demand for renewable energy and portable electronic devices in modern society, electrochemical energy storage technology, especially battery technology, has become a hot topic of research. As efficient energy storage devices, lithium-ion batteries (LIBs) and sodium-ion batteries (SIBs) have attracted much attention due to their high energy density, long cycle life, and efficient charge and discharge performance. Although lithium-ion batteries dominate in many applications, the demand for alternative technologies is becoming more and more urgent due to the scarcity and increasing cost of lithium resources.
[0003] Sodium-ion batteries are a promising alternative to lithium-ion batteries due to the abundance of sodium resources, low cost, and environmental friendliness. Sodium-ion batteries are similar to lithium-ion batteries in their working principles, but due to the larger radius and heavier mass of sodium ions, sodium-ion batteries face more challenges in material selection and performance optimization. Therefore, the development of high-performance sodium-ion battery cathode materials has become the focus of current research.
[0004] Sodium vanadium fluorophosphate (Na3V2(PO4)2F3), as a new type of sodium ion battery positive electrode material, has attracted widespread attention due to its high theoretical capacity (about 128mAh / g), stable structure and good cycle performance. However, the poor conductivity of Na3V2(PO4)2F3 itself limits its electrochemical performance under high-rate conditions. Although carbon coating is an effective method to improve the conductivity of sodium vanadium fluorophosphate materials, how to obtain a uniform and dense carbon coating layer remains a difficult problem. At the same time, when preparing sodium vanadium fluorophosphate nanoparticles, particle agglomeration is prone to occur, which will lead to a decrease in the specific surface area of the material, affecting the efficiency of the electrochemical reaction and battery performance. Summary of the invention
[0005] The purpose of the present invention is to solve the problems of sodium vanadium fluorophosphate, a positive electrode material of a sodium ion battery, being easy to agglomerate and unevenly coated with carbon, and to provide a sodium vanadium fluorophosphate nanofiber positive electrode composite material and its preparation method and application. The present invention can effectively reduce vanadium ions in a vanadium source by using a polyphenol compound as a reducing agent. After electrostatic spinning, the phenolic hydroxyl group (-OH) in the polyphenol compound can react with the cyano group (-CN) or other groups in polyacrylonitrile to form an ether bond or an ester bond. The formation of these chemical bonds can promote the combination between polyacrylonitrile and polyphenol, and enhance the interaction between the internal nanoparticles and the external nanofibers. The sodium vanadium fluorophosphate nanoparticles will be uniformly coated inside the nanofibers, thereby reducing the agglomeration of the sodium vanadium fluorophosphate particles. In addition, the grid-like nanofiber structure has excellent electrical conductivity and a larger specific surface area, which helps to improve the electrical conductivity and structural stability of the positive electrode material, and further improve the energy density and rate performance of the battery.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a sodium vanadium fluorophosphate nanofiber positive electrode composite material, the method comprising:
[0008] S1, first add a vanadium source and a reducing agent into deionized water and stir, then add a sodium source, a phosphorus source, a fluorine source and a solvent N,N-dimethylformamide, and continue stirring to obtain a solution A; dissolve polyacrylonitrile in the N,N-dimethylformamide solvent, heat and stir to obtain a solution B;
[0009] S2, mixing solution A and solution B to obtain an electrospinning solution, and then using an electrospinning machine to perform electrospinning to obtain a nanofiber positive electrode composite material precursor;
[0010] S3, placing the nanofiber positive electrode composite material precursor described in S2 in a tubular furnace for sintering, and finally obtaining a sintered product which is a sodium vanadium fluorophosphate nanofiber positive electrode composite material.
[0011] Preferably, in step S1, the vanadium source is one or more of vanadium pentoxide and ammonium metavanadate; the reducing agent is a polyphenol compound; the sodium source is one or more of sodium fluoride, sodium dihydrogen phosphate, disodium hydrogen phosphate and sodium carbonate; the phosphorus source is one or more of sodium dihydrogen phosphate, ammonium dihydrogen phosphate and phosphoric acid; the fluorine source is one or more of sodium fluoride and ammonium fluoride.
[0012] Preferably, the polyphenol compound is one or more of tea polyphenols, chlorogenic acid, tannic acid, gallic acid, and dopamine.
[0013] Preferably, in step S1, the dosage ratio of the sodium source, vanadium source, phosphorus source, fluorine source, reducing agent, deionized water and N,N-dimethylformamide in the solution A is 1.5-3mmol:1-2mmol:2mmol:3mmol:0.3-3mmol:5-10mL:5-10mL; the dosage ratio of polyacrylonitrile and N,N-dimethylformamide in the solution B is 1-5g:25-30mL.
[0014] More preferably, in step S1, the amounts of the sodium source, vanadium source, phosphorus source, fluorine source, reducing agent, deionized water and N,N-dimethylformamide in the solution A are preferably 3 mmol: 1 mmol: 2 mmol: 3 mmol: 0.3 mmol: 6 mL: 6 mL; the amounts of polyacrylonitrile and N,N-dimethylformamide in the solution B are preferably 3 g: 27 mL.
[0015] Preferably, in step S1, the heating temperature is 50-100°C, and the stirring time is 0.5-5h.
[0016] More preferably, in step S1, the heating temperature is 60-90°C, and the stirring time is 0.5-2h.
[0017] Preferably, in step S2, the distance between the electrospinning needle and the aluminum foil collector is 15-20 cm, the electrospinning voltage is 10-20 kV, and the spinning solution output rate is 10-20 μL·min -1 .
[0018] More preferably, in step S2, the distance between the electrospinning needle and the aluminum foil collector is 16-18 cm, the electrospinning voltage is 13-17 kV, and the spinning solution output rate is 14-18 μL·min -1 .
[0019] Preferably, in step S3, the sintering temperature is 500-800° C. and the sintering time is 5-12 hours.
[0020] More preferably, in step S3, the sintering temperature is 600-700° C. and the sintering time is 5-7 hours.
[0021] A sodium vanadium fluorophosphate nanofiber positive electrode composite material prepared by the above preparation method, wherein the sodium vanadium fluorophosphate particles in the sodium vanadium fluorophosphate nanofiber positive electrode composite material are uniformly coated inside the nanofiber to form a continuous fiber mesh structure. In the electrostatic spinning process, polyacrylonitrile is dissolved in an organic solvent (such as N, N-dimethylformamide) to form an electrostatic spinning solution, and nanofibers are formed after the electrostatic spinning process. A vanadium source, a sodium source, a phosphorus source, and a fluorine source are calcined to generate sodium vanadium fluorophosphate (Na3V2(PO4)2F3) nanoparticles, which are embedded or coated in the nanofibers. As a reducing agent, polyphenol compounds can react with polyacrylonitrile to promote subsequent carbonization to generate conductive nanofibers.
[0022] An application of the sodium vanadium fluorophosphate nanofiber positive electrode composite material prepared by the above preparation method is used to prepare a sodium ion battery positive electrode material, wherein the sodium ion battery positive electrode is composed of the sodium vanadium fluorophosphate nanofiber positive electrode composite material, conductive carbon black and polyvinylidene fluoride; the mass ratio of the sodium vanadium fluorophosphate nanofiber positive electrode composite material, conductive carbon black and polyvinylidene fluoride is 7:2:1.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. Compared with other reducing agents (such as citric acid), polyphenol compounds will produce free radicals during the material preparation process. The phenolic hydroxyl group (-OH) in the polyphenol compounds can react with the cyano group (-CN) or other groups in polyacrylonitrile to form ether bonds or ester bonds. The formation of these chemical bonds will promote the combination between polyacrylonitrile and polyphenols, and enhance the interaction between the internal nanoparticles and the external nanofibers. At the same time, polyphenol compounds and polyacrylonitrile will form aromatic conjugated structures during the carbonization process. The aromatic rings of the two are coupled to each other through the π-π stacking effect. The coupling of the aromatic ring structure increases the conjugation degree of the material, and the conductivity, stability and coating of the material are further enhanced after high-temperature carbonization. The specific capacity of the material is maintained at 110.3mAh·g at charge and discharge rates of 0.5C, 2C, 5C, and 10C, respectively. -1 、97.7mAh·g -1 、86.6mAh·g -1 、68.7mAh·g -1 .
[0025] 2. The nanofibers prepared by the electrospinning process can tightly encapsulate the sodium vanadium fluorophosphate particles to form a uniformly distributed fibrous structure. The coating of the nanofibers can not only prevent the agglomeration of the particles, but also effectively improve the structural stability of the material. As a carrier, the volume expansion of the active material is limited, thereby extending the cycle life of the battery. After 200 cycles, the capacity retention rate is still 93.6%.
[0026] 3. The three-dimensional mesh structure formed by nanofibers can effectively improve the conductivity and structural stability of the electrode. The pores in the mesh structure can provide more ion transmission channels in the electrode material and improve the electrochemical performance of the electrode material. At the same time, this structure can enhance the stability of the electrode material and slow down the deformation or pulverization of the battery during repeated charge and discharge.
[0027] 4. The sodium vanadium fluorophosphate nanofiber positive electrode composite material obtained by the present invention has a high specific surface area and high conductivity, which helps to quickly conduct electrons and ions and improve the overall cycle efficiency and power density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the SEM microstructure diagram of Example 1;
[0029] Figure 2 It is the rate performance diagram of Example 1 and Example 2. DETAILED DESCRIPTION
[0030] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the protection scope of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0031] Example 1
[0032] A method for preparing a sodium vanadium fluorophosphate nanofiber positive electrode composite material, the specific steps are:
[0033] Step 1, add 182 mg of vanadium pentoxide and 84 mg of tea polyphenols to 6 mL of deionized water, stir at a constant temperature of 80°C for 0.5 h, then add 126 mg of sodium fluoride, 230 mg of ammonium dihydrogen phosphate and 6 mL of N, N-dimethylformamide to the deionized water, continue heating and stirring at 80°C for 0.5 h to obtain solution A; add 3 g of polyacrylonitrile to 27 mL of N, N-dimethylformamide solvent, heat and stir at 80°C for 2 h to obtain solution B.
[0034] Step 2: Evenly mix solution A and solution B in step 1 to obtain an electrospinning solution, place the electrospinning solution in a syringe, set the distance between the electrospinning needle and the aluminum foil collector to 16 cm, the electrospinning voltage to 15 kV, and the spinning solution output rate to 16 μL min -1 After electrospinning is completed, the nanofiber positive electrode material precursor is obtained.
[0035] Step 3, drying the nanofiber cathode material precursor obtained in step 2, placing it in a tubular furnace, sintering it at 700° C. under nitrogen protection for 6 hours, and naturally cooling it to room temperature to obtain the final product, sodium vanadium fluorophosphate nanofiber cathode composite material.
[0036] The structure of the sodium vanadium fluorophosphate nanofiber cathode composite material was characterized. Figure 1 As shown, the nanofibers can tightly wrap the sodium vanadium fluorophosphate particles therein to form a uniformly distributed fibrous structure.
[0037] Application test: After mixing and grinding the sodium vanadium fluorophosphate nanofiber positive electrode composite material, conductive carbon black and polyvinylidene fluoride in a mass ratio of 7:2:1, add an appropriate amount of solvent NMP to make a slurry, then apply it on aluminum foil and dry it to obtain the positive electrode sheet. In the glove box, the positive electrode sheet, sodium sheet negative electrode, glass fiber diaphragm and electrolyte are assembled into a button battery with a battery shell, and the test is carried out after standing for 12 hours.
[0038] Example 2
[0039] A method for preparing a sodium vanadium fluorophosphate nanofiber positive electrode composite material, the specific steps are:
[0040] Step 1, add 182 mg of vanadium pentoxide and 106 mg of chlorogenic acid to 6 mL of deionized water, stir at a constant temperature of 80°C for 0.5 h, then add 126 mg of sodium fluoride, 230 mg of ammonium dihydrogen phosphate and 6 mL of N, N-dimethylformamide to the deionized water, continue heating and stirring at 80°C for 0.5 h to obtain solution A; add 3 g of polyacrylonitrile to 27 mL of N, N-dimethylformamide solvent, heat and stir at 80°C for 2 h to obtain solution B.
[0041] Step 2, step 3 and application test are consistent with Example 1.
[0042] Comparative Example 1
[0043] A method for preparing a sodium vanadium fluorophosphate nanofiber positive electrode composite material, the specific steps are:
[0044] Step 1, add 182 mg of vanadium pentoxide and 190 mg of citric acid to 6 mL of deionized water, stir at a constant temperature of 80° C. for 0.5 h, then add 126 mg of sodium fluoride, 230 mg of ammonium dihydrogen phosphate and 6 mL of N, N-dimethylformamide to the deionized water, continue heating and stirring at 80° C. for 0.5 h to obtain solution A; add 3 g of polyacrylonitrile to 27 mL of N, N-dimethylformamide solvent, heat and stir at 80° C. for 2 h to obtain solution B.
[0045] Step 2, step 3 and application test are consistent with Example 1.
[0046] Comparative Example 2
[0047] A method for preparing a sodium vanadium fluorophosphate nanofiber positive electrode composite material, the specific steps are:
[0048] Step 1: Add 182 mg of vanadium pentoxide to 6 mL of deionized water, stir at a constant temperature of 80°C for 0.5 h, then add 126 mg of sodium fluoride, 230 mg of ammonium dihydrogen phosphate and 6 mL of N,N-dimethylformamide to the deionized water, continue heating and stirring at 80°C for 0.5 h to obtain solution A; add 3 g of polyacrylonitrile to 27 mL of N,N-dimethylformamide solvent, heat and stir at 80°C for 2 h to obtain solution B.
[0049] Step 2, step 3 and application test are consistent with Example 1.
[0050] Comparative Example 3
[0051] A method for preparing a sodium vanadium fluorophosphate positive electrode composite material, comprising the following specific steps:
[0052] Step 1 is the same as step 1 of Example 1
[0053] Step 2, uniformly mix solution A and solution B obtained in step 1, dry the mixed solution in an oven for 12 hours to remove the solvent, place the dried material in a tubular furnace, sinter at 700° C. under nitrogen protection for 6 hours, and naturally cool to room temperature to obtain the final product, sodium vanadium fluorophosphate positive electrode composite material.
[0054] Application test: consistent with Example 1.
[0055] Table 1 shows the specific capacity values of the embodiments and comparative examples at different rates, and the specific capacities at 0.5C, 2C, 5C, 10C and 0.5C were tested in turn. As the rate increases, the specific capacities of the embodiments and comparative examples all decrease to varying degrees. When the current density returns to 0.5C, the specific capacities of Embodiment 1, Embodiment 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are 95.9%, 92.8%, 88.5%, 79.4% and 88.9% of their initial capacities, respectively. It can be seen that after the carbon coating of polyphenol compounds and the electrospinning process of Embodiment 1 and Embodiment 2, the reversible capacity retention rate is significantly higher than that of the comparative example.
[0056] Table 1
[0057]
[0058] Table 2 is a graph of the specific capacity of the embodiments and comparative examples after 200 cycles at a 1C rate. After 200 cycles, the capacity retention rates of Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are 89.3%, 89.1%, 85.3%, 82.8% and 86.7%, respectively. It can be concluded that the carbon layer formed after carbonization of citric acid used in Comparative Example 1 is not as uniform and dense as the polyphenol carbon layer, which affects the cyclic stability of the material. Comparative Example 2 did not use a reducing agent to reduce the vanadium source, and the oxidation state of vanadium may change significantly during the cycle, causing irreversible damage to the lattice structure, resulting in rapid decay of the material capacity. Comparative Example 3 did not perform an electrospinning process, and the capacity after 200 cycles was slightly worse than that of Example 1, indicating that the nanofiber structure can enhance the structural stability of the material to a certain extent, reduce the impact of volume change, and thus improve the cyclic stability.
[0059] Table 2
[0060]
Claims
1. A method for preparing a sodium vanadium fluorophosphate nanofiber positive electrode composite material, characterized in that: The method is: S1, first add a vanadium source and a reducing agent into deionized water and stir, then add a sodium source, a phosphorus source, a fluorine source and a solvent N,N-dimethylformamide, and continue stirring to obtain a solution A; dissolve polyacrylonitrile in the N,N-dimethylformamide solvent, heat and stir to obtain a solution B; S2, mixing solution A and solution B to obtain an electrospinning solution, and then electrospinning to obtain a nanofiber positive electrode composite material precursor; S3, sintering the nanofiber positive electrode composite material precursor described in S2 to finally obtain the sodium vanadium fluorophosphate nanofiber positive electrode composite material.
2. The method for preparing the sodium vanadium fluorophosphate nanofiber positive electrode composite material according to claim 1, characterized in that: In step S1, the vanadium source is one or more of vanadium pentoxide and ammonium metavanadate; the reducing agent is a polyphenol compound; the sodium source is one or more of sodium fluoride, sodium dihydrogen phosphate, disodium hydrogen phosphate and sodium carbonate; the phosphorus source is one or more of sodium dihydrogen phosphate, ammonium dihydrogen phosphate and phosphoric acid; the fluorine source is one or more of sodium fluoride and ammonium fluoride.
3. The method for preparing the sodium vanadium fluorophosphate nanofiber positive electrode composite material according to claim 2, characterized in that: The polyphenol compound is one or more of tea polyphenols, chlorogenic acid, tannic acid, gallic acid and dopamine.
4. The method for preparing the sodium vanadium fluorophosphate nanofiber positive electrode composite material according to claim 1, characterized in that: In step S1, the amount ratio of the sodium source, vanadium source, phosphorus source, fluorine source, reducing agent, deionized water and N,N-dimethylformamide in the solution A is 1.5-3mmol:1-2mmol:2mmol:3mmol:0.3-3mmol:5-10mL:5-10mL; the amount ratio of polyacrylonitrile and N,N-dimethylformamide in the solution B is 1-5g:25-30mL.
5. The method for preparing the sodium vanadium fluorophosphate nanofiber positive electrode composite material according to claim 1, characterized in that: In step S1, the heating temperature is 50-100°C and the stirring time is 0.5-5h.
6. The method for preparing the sodium vanadium fluorophosphate nanofiber positive electrode composite material according to claim 1, characterized in that: In step S2, the distance between the electrospinning needle and the aluminum foil collector is 15-20 cm, the electrospinning voltage is 10-20 kV, and the spinning solution output rate is 10-20 μL·min -1 .
7. The method for preparing the sodium vanadium fluorophosphate nanofiber cathode composite material according to claim 1, characterized in that: In step S3, the sintering temperature is 500-800°C and the sintering time is 5-12 hours.
8. A sodium vanadium fluorophosphate nanofiber positive electrode composite material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The sodium vanadium fluorophosphate particles in the sodium vanadium fluorophosphate nanofiber positive electrode composite material are uniformly coated inside the nanofibers to form a continuous fiber network structure.
9. An application of a sodium vanadium fluorophosphate nanofiber cathode composite material prepared by the preparation method according to any one of claims 1 to 7, characterized in that: Used to prepare a positive electrode material for a sodium ion battery, the positive electrode of the sodium ion battery is composed of a sodium vanadium fluorophosphate nanofiber positive electrode composite material, conductive carbon black and polyvinylidene fluoride; the mass ratio of the sodium vanadium fluorophosphate nanofiber positive electrode composite material, conductive carbon black and polyvinylidene fluoride is 7:2:1.